Avian Reovirus σB Interacts with Caveolin-1 in Lipid Rafts during Dynamin-Dependent Caveolae-Mediated Endocytosis - Yuyang Wang; Yangyang Zhang; Wei Zuo; Zongyi Bo; Chengcheng Zhang; Xiaorong Zhang; Yantao Wu (Viruses, 2022)
Caveolin-1 (Cav-1) is the basic component of caveolae, a specialized form of lipid raft that plays an essential role in endocytic viral entry. However, the evidence of direct involvement of caveolae and Cav-1 in avian reovirus (ARV) entry remains insufficient. In this study, the membrane lipid rafts were isolated as detergent-resistant microdomains (DRMs) by sucrose gradient centrifugation, and the capsid protein σB of ARV was found to associate with Cav-1 in DRMs fractions. Additionally, the interaction between ARV σB protein and Cav-1 was demonstrated by immunofluorescence co-localization and co-immunoprecipitation assays. Furthermore, we found that the internalization of ARV is sensitive to caveolae and dynamin inhibitors, while it is insensitive to clathrin inhibitors. In conclusion, these results indicate that the ARV σB protein interacts with Cav-1 during dynamin-dependent caveolae-mediated endocytosis for the entry of ARV.